NUMERICAL ANALYSIS OF WINDOW OPENINGS AS VENTILATION FOR 3-STOREY BUILDINGS IN A TROPICAL AREA - Okky Hendra Hermawan; Laksana Putra Ramadhan; Irfan Santosa (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
Building form has a significant influence on energy efficiency, especially in tropical regions where minimizing cooling demand is crucial. Natural ventilation is widely recognized as a passive strategy to reduce energy use while maintaining indoor comfort; however, limited research has integrated experimental validation and CFD analysis in tropical institutional buildings. This study investigates the effect of window openings on airflow and thermal distribution in a three-story library building in Pemalang, Central Java, Indonesia. Field measurements and CFD simulations were conducted, with validation showing good agreement (RMSE = 0.69). Results indicated that while the first floor achieved adequate circulation and stable temperatures, the upper floors experienced stagnation zones and higher indoor heat accumulation, suggesting suboptimal natural ventilation. Parametric simulations demonstrated that square pivot windows at 60° and 90° provided the most effective performance, improving airflow and reducing indoor temperatures. The findings highlight the importance of optimized window design as a passive cooling strategy to enhance thermal comfort and energy efficiency in tropical buildings without reliance on mechanical systems.